Organization of Sustainable Corporate Interaction in Business-Ecosystems - V. A. Kirillova (Вестник Российского экономического университета имени Г. В. Плеханова)
Topicality of the subject is stipulated by the necessity of working-out algorithms to identify stakeholders and channels of communication with them, which could help cut costs and control risks present in the process in general and within the frames of business-ecosystems in particular. The article describes in detail the process of corporate interaction and identifies structure of its key stages. By analyzing the current approaches to organization of corporate interaction provided in a number of academic works the author put forwards a matrix, which shows the structure of mutually beneficial exchange of resources and profits for participants of corporate interaction. This analysis gives an opportunity to find out stakeholders’ interests, understanding of which can lead to the balance underlying the efficient corporate interaction. Using the conclusions on nature of the interaction process the author elaborated methodology of building technologies of sustainable corporate interaction in business-ecosystems.